Altered expression of mucins throughout the colon in ulcerative colitis. Issue 2 (February 1997) - Smithson, J E; Campbell, A; Andrews, J M; Milton, J D; Pigott, R; Jewell, D P
Abstract : BACKGROUND/AIMS: Regional differences in the biology of the colonic epithelium may determine the extent of involvement by ulcerative colitis. Novel monoclonal antibodies (MAbs) were used in this study to investigate regional heterogeneity in the colonic mucosa. METHODS: MAbs generated using a method of tolerisation against common antigens in the proximal colon and distal colon were used for immunoperoxidase staining, comparative histochemistry, immunoblotting, and slot-blot analysis. RESULTS: The colon specific MAbs 5F1 (IgG3) and 6G4 (IgM) stained goblet cell contents throughout the normal distal colon but staining was markedly reduced in the proximal colon (p < 0.0001). In the distal colon of patients with ulcerative colitis, whether quiescent or actively inflamed, reactivity was reduced compared with controls (p < 0.05, p < 0.001 respectively). By contrast, an overall increase in staining was seen in the uninflamed proximal colon in ulcerative colitis compared with controls (p < 0.02). Comparative staining with high iron diamine and biochemical analyses indicated that MAb 6G4 was reactive with mucin bearing sulphate or O-acetylated sialic acid groups, or both. CONCLUSIONS: Regional differences in the staining characteristics of normal colonic mucin have been shown using novel monoclonal antibodies. The pattern of mucin expression throughout the colon in ulcerative colitis is altered even in the absence of histological changes.